Income distribution and growth's ability to reduce poverty: Evidence from rural and urban African economies - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The present study examines the degree to which income distribution affects the ability of economic growth to reduce poverty, based on 1990s data for a sample of rural and urban sectors of African economies. Using the basic needs approach, an analysis-of-covariance model is derived and estimated, with the headcount, gap and squared gap poverty ratios serving as the respective dependent variables and the Gini coefficient and PPP-adjusted incomes as explanatory variables. The study finds that the responsiveness of poverty to income growth is a decreasing function of inequality, albeit at varying rates for the three poverty measures: lowest for the headcount, followed by the gap and fastest for the squared gap. The ranges for the income elasticity in the sample are estimated at: 0.02-0.68, 0.11-1.05 and 0.10-1.35, respectively, for these poverty measures. Furthermore while, on average, the responsiveness of poverty to income growth appears to be the same between the rural and urban sectors, there are substantial sectoral differences across countries. The results suggest the need for country-specific emphases on growth relative to inequality, with special attention accorded the possible rural-urban dichotomy.
Keywords: D31; I32; O49; 330; Income distribution; income growth; poverty; rural and urban African economies